From Grid Dependence to Energy Autonomy: Case of an Urban District in Colorado-Usa - Gonzalez-Andres, A (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
Urban buildings represent a major source of energy demand worldwide, positioning them as critical elements in strategies aimed at effective energy transformation. The implementation of local renewable energy solutions and energy autonomy models becomes increasingly relevant. This paper investigates different autonomy strategies both individual and shared within a district located in Colorado, USA. To carry out this analysis, we use EnergyPlus simulations combined with MATLAB (R). Three scenarios are examined: full reliance on the electrical grid, decentralized photovoltaic panels (PV) systems and a centralized configuration that incorporates shared PV generation and a district-level battery. The model takes into account local climate conditions, building typologies, occupancy schedules, and solar availability. The results show that photovoltaic systems should come with storage to fulfill the needs, take advantage of PV production and minimize the needs from the grid. Finally, storage needs increase nonlinearly with autonomy rising from a storage to grid ratio of 2% and 104% at 25% and 75% autonomy, respectively. Centralized systems outperform decentralized ones, achieving higher autonomy with lower storage requirements by enabling energy redistribution. The findings demonstrate that centralized cooperative strategies, coupled with optimized storage, offer a promising pathway to reduce grid dependence and enhance energy resilience in urban districts.